2020
DOI: 10.1007/s00268-020-05718-5
|View full text |Cite
|
Sign up to set email alerts
|

Damage Control Laparotomy: High‐Volume Centers Display Similar Mortality Rates Despite Differences in Country Income Level

Abstract: Background Comprehensive analysis of trauma care between high-, middle-, and low-income countries (HIC/MIC/ LIC) is needed to improve global health. Comparison of HIC and MIC outcomes after damage control laparotomy (DCL) for patients is unknown. We evaluated DCL utilization among patients treated at high-volume trauma centers in the USA and South Africa, an MIC, hypothesizing similar mortality outcomes despite differences in resources and setting. Methods Post hoc analysis of prospectively collected trauma da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
8
1
Order By: Relevance
“…In absolute terms, DH potentially has a greater hemostatic effect than DCL. reported that the in-hospital mortality rate of patients who underwent DCL in high-income countries was 29% (12). Even though these studies excluded patients with cardiac arrest on admission or intra-operative death, the present outcomes including patients with cardiac arrest or intra-operative death were superior to these reports.…”
Section: Discussioncontrasting
confidence: 57%
“…In absolute terms, DH potentially has a greater hemostatic effect than DCL. reported that the in-hospital mortality rate of patients who underwent DCL in high-income countries was 29% (12). Even though these studies excluded patients with cardiac arrest on admission or intra-operative death, the present outcomes including patients with cardiac arrest or intra-operative death were superior to these reports.…”
Section: Discussioncontrasting
confidence: 57%
“…In 2017, Harvin et al reported that the mortality rate of hypotensive trauma patients undergoing emergent laparotomy was 46% (11). In 2020, Traynor et al reported that the in-hospital mortality rate of patients who underwent DCL in high-income countries was 29% (12). Even though these studies excluded patients with cardiac arrest on admission or intra-operative death, the present outcomes including patients with cardiac arrest or intra-operative death were superior to these reports.…”
Section: Discussionmentioning
confidence: 66%
“…In 2017, Harvin et al reported that the mortality rate of hypotensive trauma patients undergoing emergent laparotomy was 46% [ 10 ]. In 2020, Traynor et al reported that the in-hospital mortality rate of patients who underwent DCS in high-income countries was 29% [ 11 ]. Even though these studies excluded patients with cardiac arrest on admission or intra-operative death, the present outcomes including patients with cardiac arrest or intra-operative death were superior to these reports.…”
Section: Discussionmentioning
confidence: 99%